Pengembangan Bahan Ajar Model Mind Mapping dalam Meningkatkan Keterampilan Menulis Siswa SDN 1 Setanggor Selatan - sifaiyah; Nahdi, Khirjan; Mohzana, Mohzana (FAKULTAS TARBIYAH, 2022)
Development of Mind Mapping Model Teaching Materials in Improving Writing Skills for Students of SDN 1 Setanggor Selatan This development research aims to: (1) produce teaching materials in the form of modules to improve students' ability to make mind mapping, (2) produce appropriate modules to improve students' ability to make mind mapping, and (3) produce effective modules to improve students' abilities. in making mind maps. This development research refers to the development design steps developed by Dick & Carey (2009:6-8). The development design is grouped into five development procedures, which include (a) Requirements Analysis Phase, (b) Product Design Phase (c) Phase, (d) Validation and Evaluation (e) Final Product Phase. The product trial consisted of an alpha test conducted by two material experts and two media experts, as well as a beta test which was carried out in 2 stages, namely beta 1 test (small group trial) to 6 grade VI students and beta 2 test (large group trial). ) to 26 students of class VI. Collecting data using interview guidelines, observations, questionnaires for material experts, questionnaires for media experts, and student response questionnaires. This research (1) produces teaching materials in the form of modules equipped with instructions for use as learning resources to support Indonesian language learning, (2) the resulting product is considered very feasible to improve students' ability to make mind mapping based on the assessment of material experts, media experts, and test subjects, and (3) the resulting product is effective in increasing students' ability to make mind mapping, as evidenced by the average pretest score of 22.65, an increase in the posttest of 74.23 with a gain score of 0.71